Is periodontitis associated with halitosis? A systematic review and meta‐regression analysis. (25th August 2017) - Silva, Manuela F.; Cademartori, Mariana G.; Leite, Fábio R. M.; López, Rodrigo; Demarco, Flávio F.; Nascimento, Gustavo G.
Abstract: Aim: To systematically review the literature in order to investigate a potential association between periodontitis and halitosis. Methods: Electronic searches were performed in four different databases: PubMed, Scopus, Web of Science and Scielo. Population‐based observational studies that tested the association between periodontitis and halitosis were included. Additionally, meta‐analysis, meta‐regression and subgroup analyses were performed to synthesize the evidence. Results: A total of 1, 107 articles were identified in electronic searches; out of which, five were included within the meta‐analysis. Pooled estimates revealed that individuals with periodontitis presented 3.16 times higher odds (OR 3.16; 95% CI: 1.12–8.95) of having halitosis. Meta‐regression and subgroups analyses showed that criteria used for halitosis and periodontitis assessment explained nearly 45% and 24% of heterogeneity between studies, respectively. Conclusions: Positive association between periodontitis and halitosis was found in pooled results of population‐based observational studies. However, this evidence is derived from cross‐sectional studies.